(3JWHjbGJ CdaG aj GdeMGSHI (B/s - (3CHh GdRjJ, MSfs ((3YeGf(B: s (3OGQ UaGA(B, s, 2002)
(3fXGe GdeMGSHI GdYGeI(B-(3fXGe GdTjcGJ(B-(3fXGe GdfbO hGdUfOhb(B-(3fXGe GdCUhd GdKGHJI(B-(3fXGe GdYedGA(B-(3fXGe GdeSGgejfs
Keywords: (3GdeMGSHIs; (3GdeMGSHI(B- (3GdWQb GdQjGVjIs